AB0284 Local and systemic (ESPOIR cohort) human soluble fadd is a new inflammatory marker in rheumatoid arthritis. (23rd January 2014) - Tourneur, L.; Mistou, S.; Vilmont, V.; Cagnard, N.; Gottenberg, J.-E.; Devauchelle, V.; Chiocchia, G.
Abstract : Background: Fas-associated death domain (FADD) is the key adaptor transmitting the apoptotic signal mediated by death receptors. It is also implicated in numerous non apoptotic functions. In particular, FADD is a regulator of inflammatory processes and in rheumatoid arthritis (RA), FADD can inhibit the NF-kB inflammatory signal mediated by IL-1β and TLR4 ligands in the joint of patients. Thus, an absence of FADD expression in synoviocytes could contribute to TLR4- and IL-1R1-mediated chronic inflammation. Objectives: Recently, we identified adenosine receptors as the main regulators of a new mechanism of FADD protein expression regulation by secretion. As adenosine is abundant in the synovial fluid (SF) of RA patients, we investigated whether FADD secretion contributing to synoviocytes' FADD loss could occur in RA. Methods: We measured by sandwich-ELISA FADD protein in the sera of patients from the ESPOIR cohort [a French multi-centric cohort of patients having early arthritis lasting less than 6 months] (n=551 RA and 67 non-RA patients), from healthy individuals (n=20), and in SF from two independent cohort of patients (n=48 and n=17). FADD expression in synovial tissues and cultured synoviocytes from patients affected with RA (n=11 and n=7) and osteoarthritis (OA; n=14 and n=7) were assessed by western blot. Statistical analyses were performed by using the Student's t test. Results: FADD concentration was significantly higher in the sera of RA patients than that of the non-RA and healthy patients: 33.5±5.2 vs 10.7±1.7 (P=0.00004) and vs 5.6±2.5 ng/ml (P=0.000002), respectively. The presence of FADD in RA sera at inclusion correlated with the presence of anti-CCP antibodies (P=0.035), rheumatoid factor (P=0.03) and the DAS28 (P=0.0002) although level of FADD and rheumatoid factor or anti-CCP were not. Conversely no link could be made between FADD concentration and joint erosion at inclusion or at 2 years post-inclusion. Interestingly, taking patients diagnosed RA at inclusion, those with diagnosis maintained 2 years later had a mean FADD value of 47.3±8.8 ng/ml whereas those turning out not to be RA had a mean FADD value of 9.5±3.1 ng/ml (P=0.00006). Also we detected more FADD in SF of RA patients compared to OA patients in the two cohorts: 249.4±72.7 vs 55±17 (P=0.017) and 140.2±28.5 vs 5.8±1.4 ng/ml (P=0.0015) respectively. Preliminary results showed that cultured synoviocytes from RA patients secrete more FADD than cultured synoviocytes from OA patients. Moreover, we observed that both synovial tissues and cultured synoviocytes from RA patients expressed significantly lower level of both cytoplasmic and nuclear FADD compared to synovial tissues and cultured synoviocytes from OA patients. Conclusions: Altogether these results establish for the first time local and systemic human soluble FADD as a possible new and easily detectable inflammatory marker in RA. Additionally, these results raised the hypothesis that the loss of FADD by the joint cells could promote the inflammatory state of the joint and/or contribute to the pathogenesis of RA. References: Tourneur et al. JBC 2008. Trends in Immunol 2010. Vilmont et al. Rheumatology 2012. Disclosure of Interest: None Declared